Role of Employee-related Factors for Employee Performance in Private Sector Banks of Sindh, Pakistan - Kalwar, Muhammad Shafique; Shah, Syed Muneer Ahmed; Hussain, Nazar; Shumaila (Pakistan Journal of Humanities and Social Sciences, 2023)
The achievement of robust employee performance (EP) is a critical issue for every organization due to its significant contribution to organizational success. This study aims to examine the impact of employee-related factors on EP at private banks in Sindh, Pakistan. The researchers used quantitative methods to obtain data from private banks in Sindh at random using a survey questionnaire. The researchers distributed or delivered 528 survey forms to the various branches of Sindh's private banks. The researcher returned 318 valid surveys with a 60% response rate. The overall reliability of the questionnaire is noticed as 0.853, while individual factor reliability also appeared as greater than 0.60. The researchers used the structural equation model (SEM) to assess the hypothesized paths by analysis of moment structures (AMOS). The study findings suggest that the employee-related factors, i.e. proactivity (PA), adaptability (AD), intrinsic motivation (IM), skills flexibility (SF), commitment (CMT) and skill level (SL) significantly and positively affect EP. This study contributes to the HRM literature, particularly in the area of EP and assists the management and practitioners of human resources management and development in increasing organizational performance.